A quantifiable framework for ‘Covid-19 exposure’ to support the Vaccine prioritization and resource allocation for resource-constraint societies - Rathin Biswas; Supreeta Arya; Kavi Arya (Urban Governance, 2021)
As the pandemic COVID-19 has severely affected the entire world, it became the utmost necessity of careful prioritization and utilization of limited medical resources, especially for the resource-constraint societies. This requirement along with the asymptomatic nature of COVID-19 in a significant proportion of the population, has prompted the need for a risk assessment tool-kit that can provide a rational behind prioritization and allocation of limited available medical resources. The purpose of this study is to compose a scientific-rationale-based ‘COVID-19-Self-Assessment-Test’ (C19SAT) framework, which helps develop a basis for measuring the risk of COVID-19 exposure with self-assessment. The study comprises of two major parts- (1) identification of key components of the C19SAT framework by studying various guidelines (WHO & CDC) and relevant literature, and (2) quantification of those components by assigning weight through the analysis of survey results and opinions from medical physicians and experts. A C19SAT framework is developed to measure the risk of covid-19 exposure, comprising a set of identified components (12 parameters and their corresponding attributes) and their corresponding weights. As the scientific rationale behind such assessment framework has not been reported to date in case of available mobile applications and web-based toolkit, the present study brings the novelty and reports the construction of such a framework. The study opens up untouched research and discussion on the composition of the COVID-19 exposure-measurement framework, which can help in vaccine prioritization and resource allocation. Further studies can be carried out on refining the framework for better understanding and effectiveness towards urban health governance.